Consumer-Business Days Community-Wide Program. Project Guide No. 101. - New York State Dept. of Commerce, Albany. Woman's Program; New York State Dept. of Commerce, Albany. Woman's Program ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1976)
The project guide describes the organization and implementation of consumer-business days, a community-wide business effort in a concentrated period of time (one week to one month) in which: (1) manufacturers; retailers; and financial, trade, and service organizations provide information, literature, tours, clinics, and programs for local consumers; and (2) men's, women's, and youths' organizations, schools, colleges, libraries, civic and government agencies devote their meetings and exhibits for the period to one of these business-supplied programs. The responsibilities of the following groups and individuals involved in organizing the program are briefly discussed: general chairman, central committee, publicity, program coordinator, clubs/community groups, schools and youth, libraries, business and industry, and business and industry sub-committees. An outline of five steps involved in implementing the program and an organizational chart are also presented. The bulk of the document contains sample forms and suggestions for the program including: letters and questionnaires enlisting participation of business leaders, clubs, and youth groups; letter enclosure explaining the project; program suggestions for clubs, schools, and organizations; program suggestions for business and industry; program confirmation form; sample calendar of events (includes approximately 200 activities); and sample radio and television spot announcements. (Author/MS)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Business; Community Cooperation; Community Organizations; Community Services; Consumer Education; Program Descriptions; Program Development; Program Guides; School Business Relationship; School Community Relationship; Youth Clubs; Reports, Descriptive